Minute Treatment with Tinidazole and OrniÂ· dazole in Children with An1ebic Dysentery - Mangsang Sitepu; Chairuddin P. Lubis; A. H. Sutanto; Helena Siregar (Indonesian Pediatric Society, 1982)
At the Department of Child Health, sub-division of Gastroenterology, Pirngadi Hospirta/, Medan., 41 children were given a single dose treatment with either Tinidazole or Ornidazole. Both drugs were used in a single dose of 50 mg/kg BW. Patients -were randomly assigned to the Tinidazole regimen ( 19 children) or to the Omidazole regimen (22 children).A double blind method was used in the treatment. In both groups, clinical and parasitological cure assessed on day 4 were excellent.